Differential cytotoxicity mechanisms of copper complexed with disulfiram for combination chemotherapy in human endometrial cancer cells - Liu, Peng-Sin; Wu, Zih-Syuan; Huang, Shih-Ming (Frontiers in Oncology, 2026)
IntroductionEndometrial cancer has the highest incidence among gynecologic malignancies, with a global prevalence of 10–20%. Type II tumors are generally high-grade and recurrent. Combination chemotherapy can provide synergistic effects to combat drug resistance. The potential of using disulfiram (DSF) and copper (I or II) complexes for combination therapy remains unclear.MethodsThe cytotoxic effects of DSF, copper (I or II), and the DSF/copper complex were evaluated in two human endometrial cancer cell lines, RL95–2 and HEC-1-A, using cell viability analysis, combination index analysis, flow cytometry, immunocytochemical methods, and western blotting.ResultsCuCl2, unlike CuCl, acted synergistically with DSF to induce cytotoxicity in HEC-1-A cells, while both CuCl2 and CuCl showed synergy with DSF in RL95–2 cells. The DSF–Cu+/Cu2+ complexes induced apoptosis, lipid peroxidation, autophagy, DNA damage, and ER stress in both cell lines. The complexes increased cytosolic and mitochondrial ROS in HEC-1-A but not in RL95–2 cells. The DSF/Cu+ complex, but not DSF/Cu2+, caused mitochondrial depolarization in both lines. In combination with cisplatin or doxorubicin, only the DSF/Cu+ complex synergized with doxorubicin in RL95–2 cells. Except for CuCl with cisplatin or doxorubicin in RL95-2, DSF, CuCl, and CuCl2 synergized with these drugs in both cell lines.DiscussionThese findings indicate differential effects of CuCl and CuCl2 when complexed with DSF in human endometrial cancer cells. Given the pressing need for innovative approaches to tackle endometrial cancer, we believe our findings contribute valuable insights into the molecular interactions and therapeutic potentials of DSF/copper complexes.